1990
DOI: 10.1084/jem.171.6.2101
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gene copy number carried by different MHC ancestral haplotypes. Quantitation after physical separation of haplotypes by pulsed field gel electrophoresis.

Abstract: We have examined the hypothesis that MHC ancestral haplotypes have a specific content of genes regulating the extent of autoimmune reactions. Gene copy number was quantitated by objective densitometry after PFGE was used to separate heterozygous AHs of different lengths. Initially we analyzed examples of known gene copy number at the C4 and 21 hydroxylase loci and showed that the approach provides predictable results. We then studied heterozygotes containing one characterized and one uncharacterized AH with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…It also becomes apparent that many examples within our gene CNVs represent known genes or gene families with evidence for recent positive selection (Vallender and Lahn, 2004). This includes the defensins (Boniotto et al, 2003), the MHC region (Zhang et al, 1990), and KIRs (Hughes, 2002). Many genes from families known to be under recent positive selection but lacking previous confirmation of copy number variation CNV were detected (Supplemental Table 3).…”
Section: Detection Of Cnv Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…It also becomes apparent that many examples within our gene CNVs represent known genes or gene families with evidence for recent positive selection (Vallender and Lahn, 2004). This includes the defensins (Boniotto et al, 2003), the MHC region (Zhang et al, 1990), and KIRs (Hughes, 2002). Many genes from families known to be under recent positive selection but lacking previous confirmation of copy number variation CNV were detected (Supplemental Table 3).…”
Section: Detection Of Cnv Genesmentioning
confidence: 99%
“…It is notable that many detected whole-gene CNVs have been confirmed previously (Supplemental Table 3). These included pepsinogen (Taggart et al, 1985), amylase (Groot et al, 1989), natural killer cell receptors (Wilson et al, 2000), complement C4 (Schneider et al, 1986), HLA Class II proteins (Zhang et al, 1990), telomeric olfactory receptors (Trask et al, 1998), and low affinity Fc receptor III (Koene et al, 1998). If all detected olfactory receptor genes are included as confirmed, approximately half of all wholegene CNVs showed evidence for copy number variation from experiments outside of large-scale studies ( ϳ 30% when excluding olfactory receptors).…”
Section: Detection Of Cnv Genesmentioning
confidence: 99%
“…This region is very gene-dense and contains a number of inflammatory genes [26]. A special feature of the MHC is the strong linkage disequilibrium between alleles at a number of loci [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Particular combinations of alleles at these loci, e.g., supratypes ) such as A1, B8,BfS,C4AQO,C4B1,DRwl7,and DQw2 are associated with autoimmune disease and must carry susceptibility genes. By studying apparently unrelated individuals, we have shown that such supratypes are markers for conserved or ancestral haplotypes which have a specific genomic structure including deletions and duplications and therefore a precise gene content Tokunaga et al 1988;Collier et al 1989;Dawkins et al 1989a;Dawkins et al 1989b;Zhang et al 1990). It follows that these haplotypes have been maintained through numerous generations and therefore relate to ancestral rather than nuclear families.…”
Section: Introductionmentioning
confidence: 99%